Immunogenicity, antibody responses and vaccine efficacy of recombinant annexin B30 against Schistosoma mansoni. (21st January 2020) - Leow, Chiuan Yee; Willis, Charlene; Chuah, Candy; Leow, Chiuan Herng; Jones, Malcolm
Abstract: Aims: Schistosomes infect approximately 250 million people worldwide. To date, there is no effective vaccine available for the prevention of schistosome infection in endemic regions. There remains a need to develop means to confer long‐term protection of individuals against reinfection. In this study, an annexin, namely annexin B30, which is highly expressed in the tegument of Schistosoma mansoni was selected to evaluate its immunogenicity and protective efficacy in a mouse model. Methods and results: Bioinformatics analysis showed that there were three potential linear B‐cell epitopes and four conformational B‐cell epitopes predicted from annexin B30, respectively. Full‐length annexin B30 was cloned and expressed in Escherichia coli BL21(DE3). In the presence of adjuvants, the soluble recombinant protein was evaluated for its protective efficacy in two independent vaccine trials. Immunization of CBA mice with recombinant annexin B30 formulated either in alum only or alum/CpG induced a mixed Th1/Th2 cytokine profile but no significant protection against schistosome infection was detected. Conclusion: Recombinant annexin B30 did not confer significant protection against the parasite. The molecule may not be suitable for vaccine development. However, it could be an ideal biomarker recommended for immunodiagnostics development.